2017
DOI: 10.1038/s41598-017-11067-6
|View full text |Cite
|
Sign up to set email alerts
|

SmartFlares fail to reflect their target transcripts levels

Abstract: SmartFlare probes have recently emerged as a promising tool for visualisation and quantification of specific RNAs in living cells. They are supposed to overcome the common drawbacks of current methods for RNA analysis: the need of cell fixation or lysis, or the requirements for genetic manipulations. In contrast to the traditional methods, SmartFlare probes are also presumed to provide information on RNA levels in single cells. Disappointingly, the results of our comprehensive study involving probes specific t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
5
19
0
Order By: Relevance
“…TWIST1 transcripts were analysis by RT-PCR. Values represent the mean ± SD from duplicates or quadruplicate uptake capacity can influence the SmartFlare signal specificity (Czarnek and Bereta 2017), we decided to carefully monitor uptake in our BMSC populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…TWIST1 transcripts were analysis by RT-PCR. Values represent the mean ± SD from duplicates or quadruplicate uptake capacity can influence the SmartFlare signal specificity (Czarnek and Bereta 2017), we decided to carefully monitor uptake in our BMSC populations.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies successfully detected mRNA expression with the SmartFlare technique (McClellan et al 2015;Kronig et al 2015;Lahm et al 2015;Seftor et al 2014;Li et al 2016). However, two recent studies showed that different SmartFlare probes were not able to specifically detect their target mRNAs in cell lines and monocytes (Czarnek and Bereta 2017;Yang et al 2018). Here we showed that SmartFlare is an effective tool to detect TWIST1 gene expression in living BMSCs, but differences in probe concentration, incubation time and cellular uptake can influence the SmartFlare sensitivity and possibly lead to misinterpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the PODXL nanoprobe as the uptake control in the current studies, to determine the one-hour contact time as this used the same chemistry as all other nanoprobes examined. The common uptake control is a directly labelled, extended length sense strand as this fluoresces at all times 21 . In the current studies, we observed negligible FAM fluorescence suggesting minimal DNA degradation of the nanoprobes.…”
Section: Discussionmentioning
confidence: 99%